Формування здорового способу життя студентів ВНЗ на заняттях з фізичного виховання засобами фізкультурно-оздоровчих технологій - Рибницький, А. В.; Нестеров, О. С.; Рыбницкий, А. В.; Нестеров, А. С.; Rybnitskiy, A.; Nesterov, A. (КПУ, 2016)
UK: У статті наведено психолого-педагогічну характеристику, функції та принципи формування здорового способу життя студентів на заняттях з фізичного виховання засобами сучасних, ефективних фізкультурно-оздоровчих технологій. Виділено освітню, рекреативну й оздоровлювальну, інформаційну функції та низку принципів, які надають змогу на більш якісному рівні організувати формування здорового способу життя студентів. RU: В статье дается психолого-педагогическая характеристика, определяются функции и принципы формирования здорового образа жизни студентов на занятиях по физическому воспитанию средствами современных, эффективных физкультурно-оздоровительных технологий. Выделяются образовательная, рекреативная и оздоровительная, информационная функции и ряд принципов, позволяющих на более качественном уровне организовать процесс формирования здорового образа жизни студентов. EN: In this article description psychological and pedagogical characteristics, functions and principles of forming of the Healthy Way of Life of the Students in the process of Physical Training with using of the modern effective physical-health technologies. There are educational, recovery and healthy, informative functions, and set of principles that allow for a more qualitative level to organize the process of the Healthy Way of Life of the Students. The introduction of modern sport and recreation techniques in the educational training process of higher school (HS) students determines the validity of one of the recreation system components which should be built taking into account the basic students’ queries. Student youth is prone to the lack of physical activity – hypokinesia which precedes most common diseases. Additionally, modern life requirements, constant changeability of learning environment and production attest to the insufficiency of having a high level of education and culture, profound professional knowledge and skills, as well as to the necessity of having good health. Vital goals are impossible to achieve to the full without it. In our experiential and educational work we have identified the functions of a healthy lifestyle formation of HS students during Physical Training lessons by means of modern, effective sport and recreation techniques. These are educational, recreational and health improving, informational functions. Singling out the functions involves the use of various forms, means, sport and recreation techniques for HS practical application during sport and recreation activity.
Формирование здорового образа жизни студентов вуза на занятиях по физическому воспитанию средствами физкультурно-оздоровительных технологий
Forming of the healthy way of life of the students in the process of physical training with using of the physical-health technologies
Keywords: здоровий спосіб життя; функції; принципи; фізкультурно-оздоровча технологія; гігієнічна норма; рухова активність; здоровый образ жизни; функции; принципы; физкультурно- оздоровительная технология; healthy way of life; functions; principles; physical-health technologies